Synergetic role of TRPV4 inhibitor and mechanical loading on reducing inflammation - Babaniamansour, Parto; Jacho, Diego; Rabino, Agustin; Garcia-Mata, Rafael; Yildirim-Ayan, Eda (Frontiers in Immunology, 2025)
Resolution of inflammation is essential for normal tissue healing and regeneration, with macrophages playing a key role in regulating this process through phenotypic changes from a pro-inflammatory to an anti-inflammatory state. Pharmacological and mechanical (mechanotherapy) techniques can be employed to polarize macrophages toward an anti-inflammatory phenotype, thereby diminishing inflammation. One clinically relevant pharmacological approach is the inhibition of Transient Receptor Potential Vanilloid 4 (TRPV4). This study investigates the effects of various mechanical loading amplitudes (0%, 3%, and 6%) and TRPV4 inhibition (10 µM RN-1734) on the phenotypic commitments of pro-inflammatory (M1) macrophages within three-dimensional (3D) collagen matrices. M1 macrophages exposed to 3% mechanical strain exhibited upregulated pro-inflammatory responses, including increased pro-inflammatory gene expression and enhanced proteolytic activity within the extracellular matrix. TRPV4 inhibition partially mitigated this inflammation. Notably, 6% mechanical strain combined with TRPV4 inhibition suppressed Mitogen-Activated Protein Kinase (MAPK) expression, leading to reduced pro-inflammatory gene expression and increased anti-inflammatory markers such as CD206. Gene expression analysis further demonstrated significant reductions in pro-inflammatory gene expression and a synergistic promotion of anti-inflammatory phenotypes under TRPV4 inhibition at 6% mechanical strain. Surface protein analysis via immunohistochemistry confirmed these phenotypic shifts, highlighting changes in the expression of CD80 (pro-inflammatory) and CD206 (anti-inflammatory) markers, alongside F-actin and nuclear staining. This research suggests that TRPV4 inhibition, combined with specific mechanical loading (6%), can drive macrophages toward an anti-inflammatory state, thereby may promote inflammation resolution and tissue repair.